FIELTING SYSTEMS, INFORMATION SYSTEMS AND INFRASTRUCTURE FACILITIES ON PERFORMANCE DPRD MEMBERS PROVINCE SOUTH BORNEO - Hamdi, Hamdi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The problem in this study is whether there is an influence of filing systems, information systems and infrastructure on the performance of DPRD employees in the province of South Kalimantan. This study aims to determine whether there is influence of filing systems, information systems and infrastructure on the performance of DPRD employees in South Kalimantan Province . The population of this research is DPRD employees of South Kalimantan Province. This research is a research with a population approach so that the research sample is the population itself with a total of 30 employees as respondents. There are four variables studied in this study, namely filing systems (X1), information systems (X2), and infrastructure (X3), and the performance of DPRD employees in South Kalimantan Province (Y). Based on the results of multiple linear regression analysis calculated using SPSS, Y = 19.067 + 0.099X1 + 0.785X2 + 0.812X3 each variable, namely the filing system, information system and infrastructure on the performance of DPRD employees of the South Kalimantan Province. Simultaneous test results obtained Fcount of 44.810 with a significance of 0.000 <0.05, this means that there is an influence of filing systems, information systems and infrastructure together on the performance of DPRD employees in South Kalimantan Province. The conclusion is that partially or simultaneously the filing system, information system and infrastructure have a positive and significant effect on the performance of DPRD employees in South Kalimantan Province.